A Framework for Synergy Evaluation and Implementation in Resource Based Industries - Mohammed, Feisal Ali (Curtin University, 2016)
This thesis involved the development of a framework for identifying and reusing potential industrial waste. It evaluates the chemical composition of wastes and links it to potential surrounding industries through a generic industrial outlay. Potential waste are then analysed experimentally and through simulation for feasibility and determining mass and energy balances. The latter are used for environmental analysis through LCA and economic evaluation through AspenPlus software. Two case studies have been assessed through the framework.